Food poisoning outbreak caused by Aeromonas bacteria at a funeral in Buyengo Town Council, Jinja District, Uganda, February 2024 - Yasiini Nuwamanya; Innocent Ssemanda; Dorothy Aanyu; Brian Kibwika; Shem S. Mwebaza; Yunus Mbwire; Gorreti A. Olupot; Peruth Bamukisa; Joshua Kayiwa; Benon Kwesiga; Lilian Bulage; Richard Migisha; et al. (BMC Infectious Diseases)
Abstract Background Aeromonas bacteria are emerging human enteropathogens that cause food poisoning, with an incubation period of 12 h-7 days, typically 24–48 h. On February 15, 2024, Ministry of Health was notified of a suspected food poisoning incident in Buyengo Town Council, Jinja District, where 72 people developed gastrointestinal symptoms after a funeral. We investigated to identify the cause, magnitude and risk factors for the outbreak, to inform control and prevention measures. Methods We defined a suspected case as onset of abdominal pain and ≥ 1 of the following symptoms: diarrhea, vomiting or nausea in any person who attended the funeral of a religious leader in Buyengo TC in Jinja District during Feb 11–22, 2024. We identified cases through health facility records and community searches. We collected data using interviewer-administered questionnaires. We conducted descriptive epidemiology and environmental assessments to generate hypotheses. We conducted an unmatched case-control study among funeral attendees, and microbiology and toxicology laboratory tests on 20 case-patients and 14 environmental samples. Results We identified 65 case-patients; 5% died. Common symptoms included abdominal pain (100%), diarrhea (94%), vomiting (51%) and fever (34%). All (100%) case-patients ate at least one meal at the funeral. The epidemic curve revealed multiple peaks corresponding to the different serving times at supper and breakfast. Most cases presented within 12–86 h from Monday supper time; median incubation period was 34 h (range = 12–211 h). For both meals, beef soup served was topped-up with unboiled water and inadequately re-cooked. 62% of the cases compared to 38% of the controls ate beef stew at supper (OR = 2.7; 95%CI = 1.2–6.2). Additionally, 97% of the cases compared to 40% of the controls ate leftover beef stew for Tuesday breakfast (OR = 57; 95%CI = 5.4–600). The main source of water used at the funeral was ‘Kabakubya’ stream. Aeromonas hydrophilia and Aeromonas caviae were isolated in the gastric aspirate from one of the case-patients, and water from the stream. Conclusion This was a point source food poisoning outbreak caused by Aeromonas species at a funeral. The Aeromonas was traced to the nearby stream. Stopping use of water from the stream and enhanced water, sanitation and hygiene interventions helped control the outbreak.